ANALISIS KELAYAKAN LOGO PEMPEK CIO DALAM MEMPENGARUHI BRAND AWARENESS - Violie, Meydelin; Wijaya, Erik; Nugroho, Julius Andi (ASKARA: Jurnal Seni dan Desain, 2024)
"Pempek Cio" is one of the MSMEs that was founded in 2018 which sells typical Palembang food including typical Palembang pempek ikan tenggiri, tekwan ikan, model ikan, lenggang and mie celor. This MSME has been running for several years with a logo owned by the business. In its function, a logo becomes the identity of a business which helps people who see it to immediately recognize the business easily. Not only as an identity, a logo also functions as a medium to increase brand awareness of a business. The purpose of this analysis is to prove the suitability of the "Pempek Cio" logo in influencing Brand Awareness to customers and potential customers. The method used in this analysis begins with identifying the problem and then collecting data. After that the author conducted a literature study. These two stages will produce data that will be analyzed, the data that has been analyzed will be applied to the "Pempek Cio" logo as the main object in the proof. The author will conduct research on the general public to obtain the public's point of view to provide supporting evidence.